Electrical stimulation and swimming performance - Pichon, F.; Chatard, J. C.; Martin, A.; Cometti, G. (Medicine & Science in Sports & Exercise, 1995)
The purpose of the study was to examine the influence of a 3-wk period of electrostimulation training on the strength of the latissimus dorsi m. and the swimming performances of 14 competitive swimmers divided into 7 electrostimulated (EG) and 7 control swimmers (CG). The peak torques registered during the flexion-extension of the arm was determined with the help of an isokinetic dynamometer at different velocities (from -60 degrees.s(-1) to 360 degrees.s(-1)). Performances were measured over a 25-m pull buoy and a 50-m freestyle swim. For EG, a significant increase of the peak torques was measured in isometric, eccentric, and concentric conditions (P < 0.5). The swimming times declined significantly (P < 0.01) by 0.19 +/- 0.14 s, for the 25-m pull- buoy, and by 0.38 +/- 0.24 s, for the 50-m freestyle. For CG, no significant difference was found for any of the tests. For the whole group, the variations of the peak torques, measured in eccentric condition (-60 degrees.s(-1)) were related to the variations of the performances (r = 0.77; P < 0.01). These results showed that an electrostimulation program of the latissimus dorsi increased the strength and swimming performances of a group of competitive swimmers.